2007
DOI: 10.1038/sj.jid.5700632
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical and Pathological Features Are Associated with the BRAFT1799A(V600E) Mutation in Primary Melanoma

Abstract: The BRAF(T1799A) mutation encodes BRAF(V600E) that leads to activation of the mitogen-activated protein kinase pathway. This study aimed to assess the clinico-pathological features of primary invasive melanomas containing the BRAF(T1799A) mutation. Patients (n=251) with invasive primary melanomas from Australia were interviewed and examined with respect to their melanoma characteristics and risk factors. Independent review of pathology, allele-specific PCR for the BRAF(T1799A) mutation, immunohistochemical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
126
7
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 23 publications
18
126
7
12
Order By: Relevance
“…Most studies note indirect evidence, such as associations between mutations with anatomic site, to infer a relationship to UV exposure; however, body site alone may influence mutational status. Studies examining sun exposure questionnaire data found that BRAF-mutant melanoma was associated with high early-life ambient [228] and individual self-reported childhood sun exposure [144] and was less likely to occur in people with high cumulative sun exposure [92]. However, these results remain to be replicated.…”
Section: Sun Exposure and Tumor Subtypesmentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies note indirect evidence, such as associations between mutations with anatomic site, to infer a relationship to UV exposure; however, body site alone may influence mutational status. Studies examining sun exposure questionnaire data found that BRAF-mutant melanoma was associated with high early-life ambient [228] and individual self-reported childhood sun exposure [144] and was less likely to occur in people with high cumulative sun exposure [92]. However, these results remain to be replicated.…”
Section: Sun Exposure and Tumor Subtypesmentioning
confidence: 97%
“…BRAF-mutant melanomas are associated with young age at diagnosis, intermittently sun-exposed sites such as the trunk, superficial spreading subtype, absence of solar elastosis, and presence of mitoses [17,60,63,64,93,144,155,228]. NRAS-mutant melanomas are associated with older age at diagnosis, but less associated with specific anatomic location, are more likely to be nodular subtype, and show increased Breslow thickness and presence of mitoses [60,63,64,86,139,228,231,234].…”
Section: Clinical Characteristics Of Tumor Subtypesmentioning
confidence: 99%
“…Since that time, the 1799 T>A transversion in BRAF (V600E) has proven to be the most common somatic mutation in melanoma, accounting for half of all reported mutations [26]. Importantly, the prevalence of BRAF mutations has been shown to differ depending upon the anatomical site of the melanoma, host characteristics (such as nevus density and age) [29][30][31], levels of sun exposure in early life [32,33] and the presence or absence of contiguous neval remnants [34,35]. These observations are consistent with the divergent pathway hypothesis, but the mechanisms through which BRAF mutations arise remain unclear.…”
Section: David C Whitemanmentioning
confidence: 99%
“…BRAF, one of the three members of the RAF kinase family, has been identified as a target for cancer therapy (4,5). A sequencing screen of 923 cancer samples detected mutations in the BRAF gene in approximately 50% of human malignant melanomas and 15% of colorectal cancers (6)(7)(8)(9)(10)(11), with the V600E mutation accounting for at least 90% of oncogenic BRAF mutations (6). This V600E mutation introduces a negative charge in the BRAF kinase domain that mimics and bypasses the phosphorylation required for BRAF activation, which is normally achieved through growth factoractivated receptor tyrosine kinases.…”
Section: Introductionmentioning
confidence: 99%